Effect of management practices on mycorrhizal infection, growth and dry matter partitioning in field-grown bean Efeito de práticas culturais sobre a infecção micorrízica, crescimento e partição da matéria seca de feijão-vagem - Antonio Alberto Rocha Oliveira; Francis Edward Sanders (Pesquisa Agropecuária Brasileira, 1999)
The experiment was carried out on unsterilized field soil with low phosphorus availability with the objective of examining the effect of cultural practices on mycorrhizal colonization and growth of common bean. The treatments were: three pre-crops (maize, wheat and fallow) followed by three soil management practices ("ploughing", mulching and bare fallow without "ploughing" during the winter months). After the cultural practices, Phaseolus vulgaris cv. Canadian Wonder was grown in this soil. Fallowing and soil disturbance reduced natural soil infectivity. Mycorrhizal infection of the bean roots occurred more rapidly in the recently cropped soil than in the fallow soil. Prior cropping with a strongly mycorrhizal plant (maize) increased infectivity even further. O experimento foi realizado em solo não-esterilizado com baixo teor de fósforo. Os tratamentos foram: três pré-cultivos (milho, trigo e solo nu), seguidos por três manejos do solo (distúrbio mecânico do solo, cobertura morta e solo nu sem distúrbio no inverno). No ano seguinte à aplicação dos tratamentos, a área experimental foi semeada com Phaseolus vulgaris cv. Canadian Wonder. Os tratamentos com solo nu e o submetido a distúrbio mecânico exibiram as menores densidades de esporos de fungos micorrízicos e reduzida infecção radicular do feijoeiro. A infecção micorrízica foi maior nas parcelas anteriormente cultivadas com cereais, especialmente no pré-cultivo com milho.